Potato growth, nitrogen balance, quality, and productivity response to water-nitrogen regulation in a cold and arid environment - Su, Dandan; Zhang, Hengjia; Teng, Anguo; Zhang, Changlong; Lei, Lian; Ba, Yuchun; Zhou, Chenli; Li, Fuqiang; Chen, Xietian; Wang, Zeyi (Frontiers in Plant Science, 2024)
The pervasively imprudent practices of irrigation and nitrogen (N) application within Oasis Cool Irrigation zones have led to significant soil nitrogen loss and a marked decrease in water and nitrogen use efficiency. To address this concern, a comprehensive field experiment was conducted from April to September in 2023 to investigate the impact of varying degrees of water and fertilization regulation strategies on pivotal parameters including potato yield, quality, nitrogen balance, and water-nitrogen use efficiency. The experimental design incorporated two water deficit degrees at potato seedling (W1, 55 %-65 % of Field Capacity (FC); W2, 45 %-55 % of FC), and four distinct nitrogen application gradients (N0, 0 kg ha-1 of N; N1, 130 kg ha-1 of N; N2, 185 kg ha-1 of N; N3, 240 kg ha-1 of N). A control was also included, comprising N0 nitrogen application and full irrigation (W0, 65 %-75 % of FC), totally eight treatments and one check. The results indicated that the tuber yield, plant dry matter accumulation, plant height, plant stem, and leaf area index increased with higher nitrogen fertilizer application and irrigation volume. However, tuber starch content, vitamin C, and protein content initially increased and then decreased, while reducing sugar content consistently decreased. Except for W1N2 treatment, the irrigation water use efficiency increased as the N application rate rose, while the nitrogen partial factor productivity, crop nitrogen use efficiency and soil nitrogen use efficiency decreased with an increase in N fertilizer application. The W1N2 treatment resulted in a higher yield (43.16 t ha-1), highest crop nitrogen use efficiency (0.95) and systematic nitrogen use efficiency (0.72), while maintaining moderate levels of soil nitrate and ammonium nitrogen. Therefore, through the construction of an integrated evaluation index (IEI), the W1N2 treatment of mild water deficit (55 %-65 % of FC) at potato seedling combined with the medium nitrogen application (185 kg ha-1 of N) has the highest IEI (0.978), it was recommended as the optimal water-nitrogen regulation and management strategies to facilitate high-yield, high-efficiency, and environmentally sustainable potato production in the cold and arid oasis areas of northwest China.